Exploring the user engagement factors in computer mediated communication - Lubis, Muharman; Khairiansyah, Alfi; Adrian, Qadhli Jafar; Almaarif, Ahmad (Institute of Physics Publishing, 2019)
User engagement can be defined as the perception of the user to qualify the experience towards certain application, which focus on the positive aspects of the interaction through Internet in the context of the desire to use it continuously and for longer time. It is fundamental concept in the design of online applications regardless of the platform, driven by the observation that successful applications are not only used but those that work. However, user engagement in the technology advancement is a paradox phenomenon, as they recognize the potentiality but reluctant to adopt or they realize its use to solve problem but prefer the other solution for longer of time. The usual ways to evaluate them can be through self-report measures, observational methods, speech analysis or web analytics. These methods represent different compensations in term of configuration, the size of object and the scale of data to be collected. For example, some study might find detail and deep analysis but they are limited in term of generalizability, while the other might found out resourceful but denies the user reasoning and the context. During this millennial, the diffusion of innovation became the acceptable theory that majority academician and practical expert use to explain the phenomenon of the reason and factor to adopt certain product. Therefore, due to the assumption of several factors such as technology advancement and paradigm shift, this study want to explore current situation in the user engagement factors, which focused to computer mediated communication.